Bramwell. The complete first season [videorecording (DVD)] - Tucker, David, 1947 March 28-; Sims, Laura; Redgrave, Jemma; Calder, David, 1946-; Gainey, Keeley (Shanachie Entertainment [distributor], 2005)
Bramwell follows the fortunes of Dr. Eleanor Bramwell in her pursuit of public health and private amours in Victorian-era London. Feisty and unconventional, her sights are set on becoming a leading surgeon, an ambition unheard of for women in Victorian society.